RADIOGRAPHIC EVALUATION OF FACTORS INFLUENCING THE OUTCOME OF PRIMARY ENDODONTIC TREATMENT - Monica Monea; Alexandra Stoica; Ramona Vlad; Mihai Pop (European Scientific Journal, ESJ, 2015)
Aim of our study. The aim of our study is to evaluate the root fillings quality and the periapical status after primary endodontic treatments, based on radiographic examination, in order to identify factors that could be correlated to successful therapy. Material and methods. The sample was represented by a consecutive series of 53 patients with 71 teeth scheduled for treatment due to endodontic problems. All patients were treated under the same conditions, regarding examination protocol, materials, techniques and instrumentation. Results. From the 71 teeth, in 31(43.7%) inadequate endodontic treatments were recorded. The persistence of apical periodontitis in cases with adequate versus incorrect root fillings was 17.5% (7 teeth) and 45.16% (14 teeth) respectively (p<0.05). Conclusions. Adequate root fillings significantly reduced the prevalence of apical periodontitis. The presence of preoperative symptoms did not influence the outcome of endodontic treatment.